Dietary pattern and insulin resistance in adolescents (Research, Society and Development, 2020)
Objective: The present article seeks to correlate dietary patterns with insulin resistance in adolescents. Methods: This is a cross-sectional study with 153 adolescent students of private schools located in Picos-PI. Anthropometric, biochemical and dietary evaluations were performed. The analysis of main componentes was used to determine dietary patterns and multivariate logistic regression to correlate them with insulin resistance. Results: Insulin resistance was observed in 25.5% of the evaluated adolescents, and girls had a higher prevalence (69.2%). Four dietary patterns were identified: “Traditional”, “Western”, “Dense in energy” and “In transition”. Regarding the biochemical parameters, the “Denso em Energia” dietary pattern showed a significant correlation with blood glucose. Regarding dietary parameters, the four dietary patterns correlated significantly with energy. However, there was no correlation between dietary patterns and insulin resistance in adolescents. Conclusion: The food diversity present in each population has its own characteristics and impacts on the formation of dietary patterns and, at times, ends up making it difficult to compare studies of these patterns in different contexts, highlighting the need for more large-scale prospective studies.